The association of the blood lymphocytes to neutrophils ratio with overtraining in endurance athletes - Matsuo, K.; Kubota, M.; Sasaki, H.; Toyooka, J.; Nagatomi, R. (New Studies in Athletics, 2009)
Overtraining often compromises competitive performance in distance runners. A means for predicting overtraining in time to take corrective action may help improve training effectiveness. Overtraining is characterised by a deregulated autonomic response of the cardiovascular system and therefore assessment of the autonomic nervous system may provide the basis for such a means. The authors examined whether alterations in the ratio of blood lymphocytes to neutrophils (L/N), believed to reflect the activities of sympathetic and parasympathetic sub-systems of the autonomic nervous system, was associated with performance in four female endurance runners over an eight-month period. Blood was sampled and analysed monthly. The results were compared to performances in a series of time trials plus the runners' subjective assessments of their condition. Those who performed well had lower L/N ratios before the time trials while those who did not showed higher ratios. Although the number of subjects in the study was small, the authors conclude that the L/N ratio shows a close relationship with performance and that an increased L/N ratio may be associated with fatigue, exhaustion or stress in endurance runners.